2013
DOI: 10.1016/j.crme.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of the interdiffusion coefficient measurements of high-temperature binary mixtures under ISS conditions

Abstract: An accelerometric record from the IVIDIL experiment (ESA Columbus module) has exhaustively been studied. The analysis involved the determination of basic statistical properties as, for instance, the auto-correlation and the power spectrum (second-order statistical analyses). Also, and taking into account the shape of the associated histograms, we address another important question, the non-Gaussian nature of the time series using the bispectrum and the bicoherence of the signals. Extrapolating the above-mentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Shaking the test cell creates an additional contribution at the micro-acceleration level. A recent analysis by Saez et al (2013) indicated that only in experiments with higher frequencies, i.e. f > 1 Hz, the g rms ( f ) peaks were above the requirement curve at a forcing frequency of f 0 and its third harmonic.…”
Section: Impact Of the Microgravity Environment Onboard The Iss On DImentioning
confidence: 95%
“…Shaking the test cell creates an additional contribution at the micro-acceleration level. A recent analysis by Saez et al (2013) indicated that only in experiments with higher frequencies, i.e. f > 1 Hz, the g rms ( f ) peaks were above the requirement curve at a forcing frequency of f 0 and its third harmonic.…”
Section: Impact Of the Microgravity Environment Onboard The Iss On DImentioning
confidence: 95%